SABUN ALAMI DARI MINYAK KELAPA SOLUSI KREATIF UNTUK USAHA RUMAHAN BAGI PETANI KELAPA DI DESA RISO KECAMATAN TAPANGO KABUPATEN POLEWALI MANDAR - Fitri, Fitri; Samang, Andi Marlisa Bossa (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Riso Village, Tapango District, Polewali Mandar Regency, is one of the coconut producing areas in West Sulawesi. However, most farmers only utilize coconut as copra, which has low economic value and depends on fluctuating market prices. The lack of skills and knowledge of farmers in processing coconut derivative products and limited market access are the main problems that hinder the increase in farmers' income. The purpose of this service activity is to empower coconut farmers in Riso Village through training in making coconut oil-based natural soap, in order to increase the added value of coconut and create new business opportunities. This activity also aims to improve farmers' skills in utilizing digital technology for product marketing. The service method used includes initial observation, coordination with partners, and training activities for making natural soap and how to market it. Training includes formulation of ingredients, production techniques, packaging, and the use of social media for marketing. Evaluation was carried out using pre-test and post-test to measure the increase in knowledge and skills of participants. The result of this training is the availability of natural soap prototypes given to partners as examples for further production. This activity was also able to significantly improve farmers' understanding and skills in producing natural soap. As many as 70% of participants understand how to make natural soap, while 80% of participants understand digital marketing strategies. The natural soap products produced have great market potential because they are environmentally friendly and use local raw materials. This program is expected to improve the welfare of coconut farmers in a sustainable manner through product diversification and digital marketing optimization.